Transferring and fitting fixed-sized garments onto bodies of various dimensions and postures. (January 2019) - Jiang, Liguo; Ye, Juntao; Sun, Liming; Li, Jituo
Abstract: Many virtual try-on systems involve transferring and fitting garments to bodies of various shapes and postures, with grade preservation. To achieve this goal, garments must be treated as elastic models and their deformation is controlled by the laws of dynamics. Moreover, a collision-free state must be maintained during the simulation, as well as in the final draping state. We present a complete pipeline that concentrates on solving two problems: (1) deforming the target body towards the reference body, and (2) simulating the garment with robust handling of not only impending but also pre-existing collisions. Our solution to the first problem is a skeleton-driven framework, which consists of a collection of techniques, including skeleton embedding, skeleton posture alignment and skeleton-driven mesh deformation. For skeleton posture alignment, we decouple the orientation of each joint into two components: swing and twist, and align them separately. Treating garment models as rigid, the deformed target 'fits' into the garments with as few penetrations as possible. When solving the second problem, the body/garment penetrations are untangled along with cloth simulation, so that a collision-free state can be achieved. After that, the deformed target body restores its original shape gradually, while the garments are physically simulated to maintain a collision-free state, until a final draping state is reached on the fully restored target body. Examples show that the proposed framework is effective for garment transfer and fitness evaluation, and can be potentially used in applications like online shopping or customization. Highlights: It is the first work that guarantees grade preservation garment transfer. A skeleton-driven approach has been proposed for body deformation, so that garment simulation can be properly initialized on the deformed target body. This approach has an extra benefit of supporting character animation. The pipeline takes advantage of state-of-the-art collision response techniques so that it handles large posture variations.